2012
DOI: 10.2119/molmed.2011.00207
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cigarette Smoke Exposure and Structural Modifications on the α-1 Antitrypsin Interaction with Caspases

Abstract: α-1 Antitrypsin (A1AT) is a serpin with a major protective effect against cigarette smoke-induced emphysema development, and patients with mutations of the A1AT gene display a markedly increased risk for developing emphysema. We reported that A1AT protects lung endothelial cells from apoptosis and inhibits caspase-3 activity. It is not clear if cigarette smoking or A1AT mutations alter the caspase-3 inhibitory activity of A1AT and if this serpin alters the function of other caspases. We tested the hypothesis t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
30
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 35 publications
3
30
0
3
Order By: Relevance
“…These results are similar to previous studies which invoke A1PI-M interactions with cytosolic executioner caspases 3 and 6 [25][26], and recently caspase-1 [27], as critical for staving off cell death in endothelial cells, epithelial cells, and cardiomyocytes. As in previous studies, we observed that an excess of A1PI was required to limit caspase activity in a cell free assay, which is highly reliant on the purity and potency of the enzyme preparation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are similar to previous studies which invoke A1PI-M interactions with cytosolic executioner caspases 3 and 6 [25][26], and recently caspase-1 [27], as critical for staving off cell death in endothelial cells, epithelial cells, and cardiomyocytes. As in previous studies, we observed that an excess of A1PI was required to limit caspase activity in a cell free assay, which is highly reliant on the purity and potency of the enzyme preparation.…”
Section: Discussionsupporting
confidence: 92%
“…As in previous studies, we observed that an excess of A1PI was required to limit caspase activity in a cell free assay, which is highly reliant on the purity and potency of the enzyme preparation. One previous report showed very limited A1PI inhibition of caspase-1 enzymatic activity in a cell free enzyme assay, compared with caspase-3 and caspase-6 [26]. We note that the preparations of recombinant caspase-1 enzyme and reaction conditions used in our study were quite different and may underlie a sensitivity difference between the two assay systems.…”
Section: Discussionmentioning
confidence: 62%
“…However, the role of A1AT in endothelial cell responses to inflammation remains unclear. We and others have shown that A1AT performs an antiapoptotic function in lung endothelial cells by inhibiting executioner caspases 3, 6, and 7 (4,22,23). This activity requires an active uptake of A1AT by the lung endothelium, which normally does not produce A1AT (24).…”
mentioning
confidence: 88%
“…The most common form of a1AT deficiency is homozygous inheritance of the Z allele (lysine replacing glutamic acid 342 in the normal M allele) leading to intrahepatic polymerization of a1AT that results in reduced secretion, and, in turn, reduced serum a1AT levels (Nukiwa et al, 1986;Curiel et al, 1989;Brantly et al, 1991;Lomas et al, 1992;Carrell and Lomas, 2002;Lomas and Parfrey, 2004). Cigarette smoking markedly accelerates the disease, with diminished lifespan of about 20 years (Brantly et al, 1988a,b;Crystal et al, Sandhaus, 2009;Tuder et al, 2010;Alam et al, 2011;Lockett et al, 2012).…”
Section: Introductionmentioning
confidence: 99%